DEVELOPMENT OF A SCIENCE E-MODULE INTEGRATING THE LOCAL POTENTIAL OF BANTIMURUNG NATIONAL PARK - Nurul Mutmainnah; Lestari, Tri Kurniah; Abdulah, Abdulah; Bariyyah, Sitti Khairul (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
Abstract Science education in elementary schools requires teaching materials that not only contain concepts but also connect the material to the real environment of the students. This study aims to develop a science e-module based on the local potential of Bantimurung National Park's natural attractions as teaching materials to support science learning in line with the Merdeka Curriculum. The study used the Research and Development (R&D) method with a 4-D development model, which includes the define, design, develop, and disseminate stages, with limitations on limited trials. The research subjects involved subject matter experts, media experts, classroom teachers, and 15 fifth-grade elementary school students. Data were collected through interviews and questionnaires, then analyzed descriptively by converting the scores into qualitative categories. The results showed that the developed science e-module received a very feasible rating from subject matter experts and media experts, and was considered practical and easy to understand by teachers and students. The integration of local potential in conservation areas makes science learning more contextual and relevant to the learning experiences of students. Therefore, the science e-module based on the local potential of Bantimurung National Park is suitable for use as teaching material to support science learning in elementary schools. Keywords: Science e-module, local potential, Merdeka Curriculum, science learning, elementary school